Great food presentation 1 : more than food on a plate. - 4 0 16; 5 (Australia : Video Education Australasia)
Great food presentation 1 - This program looks at the creative skills and knowledge required to produce great food presentations in 3 different settings: an opulent function venue, a suburban hospital with many ethnic patients, a busy food training program. You'll meet people who are passionate about the food they present and genuinely care for the gastronomic experiences of their clientele. The three participants outline their diverse operations and their holistic approach to good presentation. For them, food presentation is not just food on a plate, but a whole package.;Great food presentation 2 - In this program, Julien Jane (Co-ordinator of the Council of Education's Working With Food program) shows how to imaginatively present: soup, sushi, pastry and terrine platters, main courses of fish and chicken, and dessert. Her techniques are simple, practical and easy to follow. She shows how to make best use of available resources and how small, thoughtful touches can enhance almost any food presentation.
Great food presentation 1 : more than a food on a plate ; Great food presentation 2 : a practical guide.
DVD format.
Keywords: 2 -- 0; 6; Food presentation.;Garnishes (Cookery). -- 20; 20; 2